Evaluation of Motivational Level In Order to Improve Employee Performances (Case Study: Fabrik Eatery & Bar) - Abdurrahim, Abid; Welly, John (Journal of Business and Management, 2014)
Bandung economy is mainly built upon several economic activities including tourism.One of the big attractions to tourists is the variety of interesting restaurants, cafes, and coffee houses tucked into the hills and main streets around Bandung. Every weekend, Jakartans escape the chaos and congestion of the capital to relax in the quiet Bandung hills or just to refresh their mind and souls from the chaotic traffic inside the city of Jakarta. In addition to the quality of the food and beverage, the quality of service also take a significant contribution to the popularity of the restaurants. These restaurants are without problems. This research tries to identify the problems by interview and validate by questionnaires. The purpose of the interview is to get deep understanding about the problems that occur within the restaurant while the purpose of the questionnaires were to validate the problems and analysing it tofind answers about the problems. From the result of the questionnaires that have been done, there are three categories problem analysis. First is from the behavior that we can see from MARS model. Second is from the management of Fabrik Eatery & Bar. Third is from organizational culture. This final project presents to readers a clearly vision of evaluating employee motivation with a case of Fabrik Eatery & Bar. It will also help the owners of restaurants in Bandung which may be interested on improving their business/businesses performance. Â As for the conclusion, Fabrik Eatery & Bar need to improve their employee motivation; Fabrik Eatery & Bar must fullfiled the basic needs of their employees to create a big motivation factor in order for employees to work better and harder. To achieve that, the owner and the management of Fabrik Eatery & Bar needs to understand every single problems that occur within the restaurant, also need to understand each of the employees problem and have a group discussion to solve the problems. The next step is using recommendations to solve or anticipate problems. When the recommendation are implemented, motivation level of every employees will be expected to increase afterward.Â Keywords: Motivation, Employee Motivation, MARS Model, Employee Behavior